White Cottage / White House : Irish-American masculinities and spaces of home in Hollywood cinema 1930 - 1960 - Tracy, Anthony (Trinity College (Dublin, Ireland). Department of Film, 2015)
This thesis examines constructions of Irish-American masculinity in classical Hollywood cinema's sound era (1930-1960) across five, chronologically-structured 'modes': James Cagney at Warner Bros; the Catholic priest; sport-themed biopics; the post-war urban cop; and the figure of the Irish-American returned to Ireland. I argue for such constructions to be analysed within a critical discourse of whiteness studies so as to move beyond an 'images of' approach which might too narrowly correlate such representations with the Irish-American historical experience to the exclusion of their wider cultural and ideological functions. Building on existing 'Whiteness' film scholarship of Hamilton Carroll, Richard Dyer, Ruth Frankenberg and Diane Negra and others, I argue that these masculinities function to both reconfigure and reinforce the cultural centrality and hegemony of white masculinity during historical moments of crisis and transformation.
Keywords: Drama, Film & Music, Ph.D.; Ph.D. Trinity College Dublin.